2015
DOI: 10.1002/ccd.26131
|View full text |Cite
|
Sign up to set email alerts
|

Indications and immediate and long‐term results of a novel pericardium covered stent graft: Consecutive 5 year single center experience

Abstract: PCSs were effective in the treatment of friable embolization-prone coronary plaques, sealing of acute iatrogenic vessel rupture and exclusion of large aneurysms with no thrombosis but high target lesion revascularization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 27 publications
4
14
0
Order By: Relevance
“…Covered stents have proven to be effective devices in the acute treatment of CAP. They show high sealing rate, ranging between 91% and 100%, as was also the case in our study (95.8%). Since CSs have become available, a significant decrease in emergency cardiac surgery and in‐hospital MACE has been observed .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Covered stents have proven to be effective devices in the acute treatment of CAP. They show high sealing rate, ranging between 91% and 100%, as was also the case in our study (95.8%). Since CSs have become available, a significant decrease in emergency cardiac surgery and in‐hospital MACE has been observed .…”
Section: Discussionsupporting
confidence: 87%
“…We report a high rate of ISR (29.2%), without significant difference in incidence between the PTFE and pericardium CSs. A comparable high rate is reported in other studies, ranging from 31.6% up to 54,6% in PTFE CS‐treated patients, and 26.3% in a group treated with pericardium CS. This phenomenon is probably due to altered endothelialization .…”
Section: Discussionsupporting
confidence: 87%
“…They also showed no significant difference in rates of in‐stent restenosis (ISR) . However, other studies have independently shown ISR rates as high as 54.6% for PTFE‐covered stents and 26.3% for PCS . Little evidence exists for its use for other indications; however, it has been reported as safe in the management of coronary vessel rupture and exclusion of coronary aneurysms .…”
Section: Discussionmentioning
confidence: 99%
“…Beyond this, the stent has the potential for occlusion of vessel side branches, which must be taken into account by the operator . Here, we used the pericardium covered stent to allow for effective exclusion of the pseudoaneurysm while reducing the risk of complications such as in‐stent restenosis and thrombus formation, associated with the use of bare‐metal stents and PTFE‐covered stents . Given the lack of a true aneurysm wall, coil embolisation was avoided to reduce the risk of pseudoaneurysm expansion or rupture and haemorrhage .…”
Section: Discussionmentioning
confidence: 99%
“…In the assessment, while the use of IVUS to ensure correct stent implantation and final high-pressure balloon inflation may improve the outcome [2], the use of OCT is not well established in this acute scenario and have been only probed in the assessment of pericardium covered stents and in a case reported of aneurysm post-kawasaki disease treated with polyurethane covered stent [3,4].…”
Section: Discussionmentioning
confidence: 99%